Population growth and urban expansion in the city of Salt in the period 1994 - 2015 - Wishah, Mohammad Wishah Abedel Kareem (Journal of Humanities & Social Sciences, 2020)
The research aimed to identify the population growth rates, urban expansion and the factors that affected that expansion in the city of Salt, in addition to identifying the causes of population growth and rapid urban expansion in the city of Salt, the research followed the historical approach and the inductive approach. The research reached a number of results, the most important of which is that the city of Salt has witnessed an abnormal boom in the increase in its population as a result of the wars in Palestine and the Syrian refugee, which has affected the growth of its population and the increase in its area and its urban expansion, and this has led to the multiplicity of the city’s jobs and interference in residential, artisan and industrial land uses Commercial and agricultural areas, as the population of the city of Salt developed from (61159) in 1994, while in 2015 the population reached (99890), which in turn contributed to increasing the growth of the city’s size and area, and this population increase has resulted in an unorganized urban expansion towards the main streets and mountain slopes and led to the emergence of random construction and overlapping land uses, in addition to that the research confirmed that the urban expansion in the study period (1994-2015) expanded horizontally more than perpendicular to the expense of agricultural lands.